The Interplay between Gut Microbiota and Amavata: An Ayurvedic and Modern Perspective - Naveen, A M; Elizabeth Kuruvilla, Sholly; Patil, Ashok (International Research Journal of Ayurveda & Yoga, 2025)
Amavata is a disorder characterized by the simultaneous vitiation of Ama (undigested toxic metabolic by-products) and Vata, which closely resembles rheumatoid arthritis (RA) in modern medicine. The disease manifests with pain, stiffness, swelling of joints, impaired mobility, and systemic features of inflammation. Contemporary research has increasingly highlighted the pivotal role of gut microbiota (GM) in immune modulation and the pathogenesis of autoimmune conditions, such as RA. This convergence opens a promising interface between classical Ayurvedic concepts and modern biomedical insights. From an Ayurvedic standpoint, deranged Agni (digestive fire) leads to the formation of Ama, which circulates through Srothas and accumulates in joints, triggering inflammation under the influence of vitiated Vata. Modern studies suggest that dysbiosis of GM contributes to increased intestinal permeability, altered immune tolerance, and systemic inflammation, which parallels the Ayurvedic description of Ama entering systemic circulation. Moreover, specific bacterial strains have been linked with RA pathogenesis, further strengthening the connection between gut health and joint disorders. Thus, the interplay between GM and Amavata illustrates a profound convergence of traditional Ayurvedic wisdom and modern biomedical science. Understanding this relationship offers novel integrative strategies for prevention and management, emphasizing the centrality of gut health in systemic well-being.